Editorial promoting help-seeking using E-technology for ADolescents: the ProHEAD consortium - Kaess, Michael; Bauer, Stephanie (Trials, 2019)
Mental health problems are highly prevalent in children and adolescents, but professional help-seeking behavior in this age group is extremely low. Therefore, the ProHEAD (“Promoting Help-seeking using E-technology for Adolescents”) consortium focuses on three main objectives, i.e.: (1) improving young people’s help-seeking behaviors; (2) improving the selective prevention of common disorders in those who are at risk; and (3) strengthening resources to counteract the development of mental illness. Capitalizing on Internet and mobile technology, ProHEAD delivers low threshold and easily accessible interventions to a large sample of young people. Longitudinal school-based assessments of mental health problems will be conducted at baseline and two annual follow-ups in five regions of Germany in a total sample of 15,000 children and adolescents (aged ≥ 12 years). Based on the results of their baseline assessment, participants are invited to register for one out of five sub-projects. The objectives and procedures of these five randomized controlled trials are published in this issue of Trials.
Gesehen am 04.03.2019